Fiscal decentralisation, local institutions and public goods provision: Evidence from Indonesia - Sarmistha Pal; Zaki Wahhaj (Institute for the Study of Labor (IZA), 2012)
Using data from the Indonesian Family Life Surveys, this paper studies the impact of fiscal decentralisation in Indonesia on local public spending across communities with different types of local institutions. Our results provide evidence of heterogeneity in access to public goods across communities in the period prior to fiscal decentralisation; with significantly greater spending on schools and health centres in communities which observe traditional adat laws (which promote an ethic of mutual cooperation), and less spending on roads, public transport, communications etc. in communities which have a democratic electoral system. Fiscal decentralisation led to an increase in the share of spending on physical infrastructure, as well as a convergence in spending across communities with different types of local institutions. We develop a theoretical model to argue that communities which enjoy a higher level of mutual cooperation would benefit less from investment in public goods which facilitate communication and exchange with outsiders - as these improve the outside options of community members and therefore makes it more difficult to sustain intra-community cooperation. Surprisingly, investment in communications and transport infrastructure in these communities were more restrained during the period of centralised fiscal control.
Keywords: D02; H41; O43; 330; decentralisation; democratisation; mutual co-operation; social and physical infrastructure; local public spending; Indonesia; Finanzföderalismus; Dezentralisierung; Kommunalverwaltung; Kommunale Ausgaben; Öffentliches Gut; Indonesien